2021
DOI: 10.1177/0886260520985499
|View full text |Cite
|
Sign up to set email alerts
|

Situational and Dispositional Factors in Rape Cognitions: The Roles of Social Media and the Dark Triad Traits

Abstract: Previous research has established the importance of socially aversive personality traits (i.e., the Dark Triad) in rape cognitions (operationalized here as rape-supportive attitudes, rape victim empathy, and hostile masculinity). However, less is known about how sexist social media content influences attitudes toward rape cognitions depending on the personality of the individual. In an online experiment, after completing the Short Dark Triad-3 questionnaire, participants ( N = 180) were primed with either sexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Rape myth acceptance has been found to be a major bystander barrier in previous studies, mainly in the United States (e.g. Labhardt et al., 2017 ), with some evidence from Australia ( Kania & Cale, 2018 ), Italy ( Martini & De Piccoli, 2020 ) and Ecuador ( Lyons, Brewer, et al, 2021 ). Our results showed that rape myth acceptance also prevents people from helping the victims in Indonesia, Singapore and the United Kingdom.…”
Section: Discussionmentioning
confidence: 93%
“…Rape myth acceptance has been found to be a major bystander barrier in previous studies, mainly in the United States (e.g. Labhardt et al., 2017 ), with some evidence from Australia ( Kania & Cale, 2018 ), Italy ( Martini & De Piccoli, 2020 ) and Ecuador ( Lyons, Brewer, et al, 2021 ). Our results showed that rape myth acceptance also prevents people from helping the victims in Indonesia, Singapore and the United Kingdom.…”
Section: Discussionmentioning
confidence: 93%
“…Intriguingly, only sexual fantasies involving intimacy were perceived as negative by male survivors. A study by Maniglio [74]. suggest that early traumatic experiences, particularly those related to sexual abuse during childhood, can lead to the development of psychiatric disorders or emotional distress in the future.…”
Section: Childhood Trauma and Sexual Fantasymentioning
confidence: 99%